Governando iniciativas de cidade inteligente: compreendendo os arranjos de governança sócio-técnica e o uso de tecnologias da informação nos casos de Curitiba e São Paulo - Przeybilovicz, Erico (2019)
Given the context of increasing urbanization, the increase of ICT in the urban context and the complexity of dealing with the various actors of the city, in this thesis I understand how the socio-technical governance arrangements configure the use of information technologies in the initiatives of smart city, from the perspective of urban governance and socio-technical interactions networks. The argument is that the governance of smart city initiatives emerges from the iteration between technological artifacts and social actors and traditional models of urban governance help to explain emerging arrangements. I used as a theoretical lens a combination of Social Informatics (Kling, 1999) and Socio-Technical Interaction Networks (Kling et al, 2003) with urban governance modes (Pierre, 2011). The research question that guides the research is how the socio-technical governance arrangements configure the use of information technologies in the initiatives of a smart city? To answer this question, two smart city initiatives were studied: Curitiba Collaborates in Curitiba and Pátio Digital in São Paulo. By analyzing in depth, the emergence of socio-technical networks and focusing on the understanding of the influential position of the various actors and information technology, two new governance arrangements were identified: Stimulated Collaborative Governance and Governance for Collaborative Development. There is evidence that the predominant urban governance modes in the city explain the interactions in the smart city governance network, the way these networks are built, and the use of digital technologies. The use of digital technologies appears as a result of socio-technical governance networks and the ways in which these technologies are associated with local urban governance practices. The use of ICT is the result of the dynamics of interactions between government-social actors. These interactions extrapolate the level of public administration to the level of the city within the socio-technical network. Also, the use depends on the very availability of information technology. The network of actors and digital technology are mutually constructed in the two cases analyzed. The interesting finding is that the use of digital technologies makes new governance arrangements emerge, at the same time the use of technology is a result of the governance model that emerged.